Parliamentary accountability in multilevel governance: what role for parliaments in post-crisis EU economic governance?. Issue 2 (1st February 2018) - Crum, Ben
ABSTRACT: How has the new structure of European Union (EU) economic governance affected the ability of parliaments (national and European) to scrutinize and control economic policy? Departing from the premise that executive power needs to be matched by appropriate parliamentary control, this contribution argues that parliamentary powers have been compromised in EU economic governance. Although budgetary powers remain formally at the national level, governments' decisions have become constrained and national parliaments find themselves on the losing side of a reinforced two-level game. This loss in parliamentary powers is not compensated at the European level, as at that level political authority is effectively left suspended between the national governments, who are unaccountable as a collective, and the European Commission, which lacks a political mandate of its own. Against this background, a final section identifies guidelines for organizing parliamentary accountability in settings, like EU economic governance, in which executive power has come to be shared across levels.